Pengaruh Penggunaan Platform E- Commerce Terhadap Kinerja Penjualan Toko Offline Muda Mudi di Era Digital - Rafanda, Shelly; Fitri Kurniawati; Husni Awali (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of using the e- commerce platform on the sales performance of Muda Mudi offline stores in the Digital Age. This research uses descriptive qualitative research methods with data collection methods in the form of primary and secondary data. Primary data is taken from interviews with owners and employees observation observations at the research site. And for secondary data obtained from literature studies or literature searches of previous research literature through internet sites or journals that are relevant to this case. The results of the study found that the existence of E-commerce actually made offline stores deserted customers because now people prefer to shop for fashion in online stores because they can buy it easily without coming to the store just using the internet wherever and whenever they are. Prices in online stores are sometimes also cheaper than offline stores and also usually the choice of goods in online stores is more than offline stores